Efficacy and Safety of Rotigotine Transdermal Patch on Neuropsychiatric Symptoms of Parkinson's Disease: An Updated Meta-Analysis and Systematic Review - Yan, Junqiang; Ma, Hongxia; Liu, Anran; Huang, Jiarui; Wu, Jiannan; Yang, Jianxue (Frontiers in Neurology, 2021)
Objective: The effects of rotigotine transdermal patch (RTG) on the neuropsychiatric symptoms of Parkinson's disease (PD) outcomes remain controversial. The aim of this review was to determine the efficacy and safety of RTG on the neuropsychiatric symptoms of PD. Methods: In this systematic review and meta-analysis, PubMed, Cochrane Library, EMBASE, and Web of Science were searched for randomized controlled trials comparing RTG and placebo in PD up to May 10, 2021. We analyzed the data using Review Manager 5.2 software. The quality of evidence was assessed using the Grading of Recommendations Assessment, Development, and Evaluation Approach. In order to avoid false-positive results caused by random error, we use TSA software for trial sequential analysis (TSA). Results: We included 10 studies (1,844 patients). The meta-analysis showed that, compared with placebo, RTG can significantly improve the scores for Apathy Scale (MD = −1.68, 95% confidence interval, CI: −2.74 to −0.62, P = 0.002; moderate certainty), Beck Depression Inventory-II (MD = −1.19, 95% CI: −2.26 to −0.11, P = 0.03; moderate certainty), the Non-Motor Symptoms Scale (MD = −3. 66, 95% CI: −4. 30 to −3.01, P < 0.00001; moderate certainty), the sleep/fatigue domains of the Parkinson's Disease Non-motor Symptom Assessment Scale (MD = −2.03, 95% CI: −3.08 to −0.98, P = 0.0001; moderate certainty), the mood/apathy domains of the Non-motor Symptom Scale (MD = −2.48, 95% CI: −4.07 to −0.89, P = 0.002; high certainty), the eight-item Parkinson's Disease Questionnaire (MD = −4. 93, 95% CI: −6.79 to −3.07, P < 0.00001; moderate certainty), and the 39-item Parkinson's Disease Questionnaire (MD = −3.52, 95% CI: −5.25 to −1.79, P < 0.0001; high certainty). However, there was no statistically significant difference on the Snaith–Hamilton Pleasure Scale (MD = −0.12, 95% CI: −0.58 to 0.34, P = 0.61). Our results showed that RTG exerts a positive effect on sleep. According to the TSA, the results implied that, except for the Beck Depression Inventory-II, conclusive evidence have been obtained in the RTG group. It has been proven in our meta-analysis that rotigotine has good safety and tolerability. Conclusions: RTG can effectively improve the neuropsychiatric symptoms, sleep quality, and quality of life in patients with PD.